ANALISIS PROBLEMATIKA KETERAMPILAN MENULIS IMLA’ (KITABAH) BAHASA ARAB TERHADAP SISWA KELAS VI MI NURUL HIKMAH LANTAN LOMBOK TENGAH - Mikyal Zahraturrahmah Rahman, Baiq; Gozali, Imron (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the problems of Arabic writing skills among fifth-grade students at MI Nurul Hikmah Lantan. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study show that students experience difficulties in writing Arabic texts, which are divided into two aspects, namely linguistic and non-linguistic. Linguistic challenges include difficulties in pronouncing Hijaiyah letters, limited vocabulary, weak understanding of grammar (nahwu and sharaf), and insufficient ability to construct sentences accurately. Meanwhile, non-linguistic problems include low interest and self-confidence among students, the suboptimal role of teachers in motivating learning, limited supporting facilities, and a social environment that is not conducive to the Arabic language learning process. Based on these findings, it is recommended that more interactive teaching methods be strengthened, student motivation be increased, and more effective learning facilities be utilized to support Arabic writing skills.